Collaborating with strategic partners: SHiFT’s country engagement strategy - CGIAR (CGIAR, 2024)
Transforming food systems requires strategic collaboration between stakeholders across many sectors. The CGIAR Research Initiative on Sustainable Healthy Diets through Food SystemsTransformation (SHiFT)works with partners in Viet Nam, Ethiopia, and Bangladesh to collectively catalyze targeted changes in food systems that lead to more sustainable, healthier diets. In this video, hear from Mark Lundy, SHiFT Deputy Lead, about the Initiative’s country engagement strategy.